2016
DOI: 10.1186/s12873-016-0080-7
|View full text |Cite
|
Sign up to set email alerts
|

Human temperatures for syndromic surveillance in the emergency department: data from the autumn wave of the 2009 swine flu (H1N1) pandemic and a seasonal influenza outbreak

Abstract: BackgroundThe emergency department (ED) increasingly acts as a gateway to the evaluation and treatment of acute illnesses. Consequently, it has also become a key testing ground for systems that monitor and identify outbreaks of disease. Here, we describe a new technology that automatically collects body temperatures during triage. The technology was tested in an ED as an approach to monitoring diseases that cause fever, such as seasonal flu and some pandemics.MethodsTemporal artery thermometers that log temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
(28 reference statements)
2
9
0
Order By: Relevance
“…14,15 The Boston data were initially collected to assess fever incidence as a means of tracking disease outbreaks (syndromic surveillance). 16 We also observed that mean body temperature followed a consistent diurnal cycle across days of the week and seasons of the year in the Boston ED. 17 These results suggested that it would be useful to study how body temperature cycles relate to fever presentation.…”
Section: Study Planningsupporting
confidence: 62%
“…14,15 The Boston data were initially collected to assess fever incidence as a means of tracking disease outbreaks (syndromic surveillance). 16 We also observed that mean body temperature followed a consistent diurnal cycle across days of the week and seasons of the year in the Boston ED. 17 These results suggested that it would be useful to study how body temperature cycles relate to fever presentation.…”
Section: Study Planningsupporting
confidence: 62%
“…A cohort study conducted by Obermeyer et al (2017) [17] in 35,488 healthy patients confirmed the daily variation and found a normal range of 35.3-37.7 • C. This study also established a negligible discrepancy of -0.03 • C of tympanic versus oral temperature [17]. Therefore, temperatures between >37.7-42 • C, were considered as pyrexia where the upper cut-off accounts for hyperpyrexia [7]. The analysis was performed on records of patients with tympanic temperature readings within the range of 32-42 • C. This excluded 0.0306% of the records (i.e.…”
Section: Data Processingsupporting
confidence: 63%
“…Both devices have a measurement range of 34-42.2 • C with an accuracy of 0.2 • C between 35.5-42 • C and 0.3 • C outside this range [12,13]. As the data included temperature readings outside the range of the device capabilities, records indicating physiological hypothermia (32 • C) [14,15] and hyperpyrexia (42 • C) [7] were excluded.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods: Temperatures (n=115,149) were collected during triages at a Boston adult emergency department to monitor outbreaks (September 2009-March 2012). 2,3 We also investigated adult triage temperatures (n=218,574) from a nationally representative study of US emergency department visits (December 2002-December 2010). 4 The thermometer types used were temporal artery (Boston) and a nationally representative sample (national).…”
Section: Fevers Are Rarest In the Morning: Could We Be Missing Infectmentioning
confidence: 99%